Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1097/00004647-199704000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of SB 206284A, a Novel Neuronal Calcium-Channel Antagonist, in Models of Cerebral Ischemia

Abstract: The effects of SB 206284A, 1-[7-(4-benzyloxyphenoxy)heptyl] piperidine hydrochloride, have been investigated in vitro on calcium and sodium currents in rat-cultured dorsal root ganglion (DRG) neurones and potassium-mediated calcium influx in rat synaptosomes. Cardiovascular hemodynamic effects in both anesthetized and conscious rats, and neuroprotective activity in in vivo cerebral ischemia models were also investigated. In the rat DRG cells, SB 206284A caused almost complete block of the sustained inward Ca2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Therefore, therapeutic strategies against calcium influx are potentially neuroprotective. Many studies have demonstrated that calcium antagonists reduce ischemic lesion volume in experimental stroke models (2)(3)(4)(5)(6). A new compound, (RS)-(3,4-dihydro-6,7-dimethoxyisoquinoline-1-␥1)-2-phenyl-N,N-di-2-(2,3,4-trimethoxyphenyl)ethyl acetamide (LOE 908 MS), is a broad-spectrum cation channel blocker that fully blocks adenosine triphosphate (ATP)-or N-formyl-L-methionyl-L-leucyl-L-phenylalanine-stimulated cation currents at 3 µM (7).…”
mentioning
confidence: 99%
“…Therefore, therapeutic strategies against calcium influx are potentially neuroprotective. Many studies have demonstrated that calcium antagonists reduce ischemic lesion volume in experimental stroke models (2)(3)(4)(5)(6). A new compound, (RS)-(3,4-dihydro-6,7-dimethoxyisoquinoline-1-␥1)-2-phenyl-N,N-di-2-(2,3,4-trimethoxyphenyl)ethyl acetamide (LOE 908 MS), is a broad-spectrum cation channel blocker that fully blocks adenosine triphosphate (ATP)-or N-formyl-L-methionyl-L-leucyl-L-phenylalanine-stimulated cation currents at 3 µM (7).…”
mentioning
confidence: 99%
“…The time at which [Ca 2+ ] s(7.4) was determined was 3.2 ± 2.1 h in group 1 and 4.3 ± 1.8 h in group 2, representing an assessment of multiple organ damage very shortly after birth. The possibility of preventing neuronal injury by blocking the influx of Ca 2+ into neurons by administering a N ‐methyl‐D‐aspartate receptor/channel antagonist (MK‐801) 24,25 or a calcium channel antagonist has been reported 26–28 . Such agents might be required immediately after birth in neonatal HIE patients, because our data suggest a substantial [Ca 2+ ] s decrease almost immediately after hypoxic–ischemic reperfusion injury occurs.…”
Section: Discussionmentioning
confidence: 81%
“…In this context, therapeutic strategies against Ca 2+ influx are considered to be potentially neuroprotective. Many studies have demonstrated that Ca 2+ antagonists reduce the size of ischemic lesions in experimental stroke models (2,3,15,37). LOE 908 was found to have neuroprotective effects on focal ischemic injury of rat brain induced by temporal (24) or permanent occlusion of middle cerebral artery (12).…”
Section: Neuroprotective Effectsmentioning
confidence: 99%